Distributional Properties and Syntactic Complexity of Adjectives in Modern Standard Arabic: A Structural Analysis of News-Based Usage - Abdul Malik, Muhammad Zulfi; Larhzizer, Fouad; Nur, Tajudin (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study examines the morphological and syntactic properties of adjectives in Modern Standard Arabic (MSA), addressing a gap in systematic analyses of their functional distribution and contrasts with nouns. The primary objectives are to (1) classify the syntactic roles of adjectives (attributive, subject, predicate, object, adverbial), (2) analyze their morphosyntactic features in each role, and (3) identify how their behavior diverges from nouns, particularly in agreement and definiteness. Employing distributional analysis and immediate constituent analysis (a method for parsing hierarchical sentence structure), we demonstrate that Arabic adjectives exhibit distinct patterns across these functions. Attributive adjectives fully agree with head nouns in gender, number, case, and definiteness. Adjectives functioning as subjects show syntactic flexibility: definite forms can independently serve as subjects, while indefinite forms require referential contexts. Predicative adjectives are invariably indefinite and shift from nominative to accusative under copular verbs (e.g., kāna). Object adjectives display definiteness and accusative/genitive case marking. Adverbial adjectives, by contrast, are obligatorily indefinite and marked with the accusative case, reflecting their role in modifying events rather than entities. Key findings reveal two contrasts with nouns: (1) adjectives enforce stricter agreement rules, and (2) their definiteness alternations (definite for objects vs. indefinite for predicates and adverbials) correlate predictably with syntactic function. The study contributes to Arabic linguistics by systematizing adjective syntax and to broader typology by illustrating how Modern Standard Arabic (MSA) encodes non-referentiality morphologically. These insights are relevant for theoretical linguistics, Arabic pedagogy, and comparative Semitic studies.